2019
DOI: 10.1002/jlcr.3755
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of the theranostic pair 177Lu‐OPS201/68Ga‐OPS202 for targeting somatostatin receptor expressing tumors

Abstract: Radiolabeled somatostatin receptor (sstr) antagonists have shown superiority in different preclinical and clinical settings compared with the well‐established and clinically used agonists for targeting sstr‐expressing tumors, with regard to pharmacokinetics, tumor uptake, and retention. The theranostic pair 177Lu‐OPS201/68Ga‐OPS202, based on the sstr2 antagonist JR11 (Cpa‐c[d‐Cys‐Aph(Hor)‐d‐Aph(Cbm)‐Lys‐Thr‐Cys]‐d‐Tyr‐NH2), is the most advanced pair of the antagonist family in terms of preclinical development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 56 publications
(115 reference statements)
1
27
0
Order By: Relevance
“…A number of preclinical and initial clinical studies (summarized in [ 17 , 18 ]) suggested improvements in both diagnostic sensitivity and therapeutic efficacy by the use of radiolabeled SST2 antagonists (i.e., DOTA-JR11) instead of agonists (i.e., DOTA-TATE or DOTA-TOC). This was attributed to different reasons, including but not limited to, the following: (a) a higher number of binding sites recognized by the antagonists on the surface of SST-expressing cells [ 19 , 20 ], with consequently higher accumulation; (b) lower uptake of the antagonists in organs that were the primary sites of metastasis (i.e., liver), enabling better lesion-to-background contrast, and as such better image sensitivity [ 4 ]; (c) longer retention of the antagonists in the tumor, leading to higher tumor radiation doses [ 3 , 21 ]; and (d) a higher number of DNA double strand breaks caused by the antagonists on SST-expressing cells [ 22 ], suggesting more effective treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A number of preclinical and initial clinical studies (summarized in [ 17 , 18 ]) suggested improvements in both diagnostic sensitivity and therapeutic efficacy by the use of radiolabeled SST2 antagonists (i.e., DOTA-JR11) instead of agonists (i.e., DOTA-TATE or DOTA-TOC). This was attributed to different reasons, including but not limited to, the following: (a) a higher number of binding sites recognized by the antagonists on the surface of SST-expressing cells [ 19 , 20 ], with consequently higher accumulation; (b) lower uptake of the antagonists in organs that were the primary sites of metastasis (i.e., liver), enabling better lesion-to-background contrast, and as such better image sensitivity [ 4 ]; (c) longer retention of the antagonists in the tumor, leading to higher tumor radiation doses [ 3 , 21 ]; and (d) a higher number of DNA double strand breaks caused by the antagonists on SST-expressing cells [ 22 ], suggesting more effective treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically used SSTR2-targeting positron emission tomography (PET) agents include, but are not limited to, [ 68 Ga]Ga-DOTA-TATE, [ 68 Ga]Ga-DOTA-TOC, and [ 68 Ga]Ga-NODAGA-JR11 [2,3]. These somatostatin analogs can be radiolabeled with beta-emitting radionuclides (e.g., lutetium-177) for peptide receptor radionuclide therapy [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, each radiotracer needs to be evaluated independently and modifications implemented accordingly to produce a “matching” pair. There are examples in the literature where the theranostic pair consists of two radiotracers that differ not only by the radiometal, but also by the conjugate, e.g., [ 68 Ga]Ga-OPS202/[ 177 Lu]Lu-OPS201 ([ 68 Ga]Ga-NODAGA-JR11/[ 177 Lu]Lu-DOTA-JR11) for SST2 [ 36 ] or 68 Ga-pentixafor/ 177 Lu-pentixather for CXCR4 [ 37 ].…”
Section: Resultsmentioning
confidence: 99%